A comparison of bioelectrical impedance analysis and air displacement plethysmography to assess body composition in children - Chen, Fangfang; Wu, Lijun; Chen, Yiren; Wang, Jing; Liu, Junting; Huang, Guimin; Hou, Dongqing; Liao, Zijun; Zhang, Ting; Xie, Xianghui; Liu, Gongshu (Frontiers in Public Health, 2023)
Background Accurate assessment of body composition (BC) is important to investigate the development of childhood obesity. A bioelectrical impedance analysis (BIA) device is portable and inexpensive compared with air displacement plethysmography (ADP) for the assessment of BC and is widely used in children. However, studies of the effectiveness of BIA are few and present different results, especially in pediatric populations. The aim of this study was to evaluate the agreement between BIA and ADP for estimating BC. Methods The BC of 981 Chinese children (3–5 years) was measured using the BIA device (SeeHigher BAS-H, China) and ADP (BOD POD). Results Our results showed that BIA underestimated fat mass (FM) and overestimated fat-free mass (FFM) in normal weight children (P < 0.05), but the opposite trend was shown in children with obesity (P < 0.05). The agreement between FM and FFM measured by the two methods was strong (CCC > 0.80). The linear regression equation of 5-year-old children was constructed. Conclusion The SeeHigher BAS-H multi-frequency BIA device is a valid device to evaluate BC in Chinese preschool children compared with ADP (BOD POD), especially in 5-year-old children or children with obesity. Further research is needed to standardize the assessment of BC in children.